The effect of educational intervention on iron and vitamin D consumption based on the theory of planned behaviour in Iranian adolescent girls: a quasi-experimental study. Issue 6 (2nd November 2019) - Alami, Ali; Tavakoly Sany, Seyedeh Belin; Tehrani, Hadi; Lael- Monfared, Elaheh; Hosseini, Zahra; Jafari, Alireza
ABSTRACT: Iron and vitamin D deficiency are the common problems in Iranian adolescents. This study aimed to examine whether the theory of planned behaviour (TPB) implemented in the educational intervention were effectiveness to improve behavioural intention to intake iron and vitamin D supplements among adolescent girls. Quasi-experimental study was used to enrol 175 adolescent girls aged 12–14 years attending community-based practices in the Gonabad, Iran. We evaluated the effects of a behavioural intervention for adolescents compared to usual care controls, on the TPB constructs and adolescent's behavioural intentions to intake vitamin D and iron supplements, assessed at baseline and post-intervention. Bivariate analysis was used to assess whether the health provider training improved outcomes. Mean scores of knowledge, attitude, subjective norm, perceived behavioural control (PBC) and behavio\ural intention before intervention were, respectively, 20.65, 25.88, 25.82, 20.12 and 11.22, and after the intervention, were, respectively, 23.74, 25.48, 18.27, 11.33 and 11.82. All the constructs except the attitude in the intervention group were significantly higher ( p < 0.001) than the control group, indicating that adolescent's behavioural intention to intake iron and vitamin D supplements significantly improved in intervention group compared control group. Therefore, constructs of the TPB could be a significant determinate to change multiple behavioural intention in different populations. Given the importance of the use of supplements by female adolescents, it is necessary to pay more attention to the issue of training in this field and to remove the existing obstacles. Abbreviations: TPB: Theory of planned behavior; PBC: perceived behavioral control; IDA: iron deficiency anemia